PENERAPAN PENDEKATAN KONTEKSTUAL DAN MODEL PEMBELAJARAN KOOPERATIF TIPE CRH PADA PEMBELAJARAN FISIKA SISWA KELAS XI IPA SMAN 1 RAMBATAN - Stephani, Ayu; Rahmi, Elvy; Asmendri, Asmendri (Jurnal Pembelajaran MIPA, 2014)
Purpose of this research is to know the result of student physics in applying of contextual approach and cooperative model type of course review hooray in class of XI IPA SMAN 1 Rambatan. The type of this Research is quasi experiment with research device in the form of randomized control group posttest only design. Research procedure differentiated into three phase that is preparation, execution and solution. Research instrument is used observation sheet and result test of learning. Analyze technique of data is used normalitas test, homogeneity test and hypothesis test. The Result of research shows the difference of average value, standard deviation and variants between experiment classes with control classes. The existence of this research is cause of the influence in applying contextual approach and cooperative model type of course review hooray. The use of this approach make students can find the material of study and connecting it with their real life situation, so that the atmosphere of class become active and pleasant. This matter can improve the understanding of student toward the material. The result of this research also shows raised hypothesis at this research is accepted, so that it can be concluded, the result of student in experiment classes which applying of contextual approach and cooperative model type of course review hooray is better than of control classes.Key words: contextual approach, cooperative learning, course review hooray, physics Study